Psychological adjustment and diabetic control. Issue 10 (October 1987) - Fonagy, P; Moran, G S; Lindsay, M K; Kurtz, A B; Brown, R
Abstract : Glycosylated haemoglobin concentrations, C peptide secretion, insulin dose, psychiatric state, intellectual functioning, and the extent to which the implementation of the diabetic regimen was shared between parent and child were studied in a cross sectional study of 50 children with diabetes aged 6-16. Indications of psychological disturbance in the children and their parents predicted low glycosylated haemoglobin concentrations in the children, and accounted for 44% of variance in blood glucose control. The child's early and independent participation in the implementation of the diabetic regimen was associated with poor control.